Safeguarding brand identity while scaling: strategic marketing for small and medium companies in the AI age - Chulayevska, Liliya (Актуальні питання економічних наук, 2026)
The rapid digital transformation of the business environment and the active implementation of artificial intelligence are changing the conditions for brand development, increasing the requirements for consistency in their positioning and communications as they expand their market presence. The purpose of the article is to substantiate strategic marketing approaches that ensure the preservation of the brand identity of small and medium-sized companies in the process of scaling in the context of transformation driven by artificial intelligence. Methods. To study current developments in the subject, a review of the scientific literature was conducted, and generalization and systematization methods were used to present the research results. Results. It was established that brand identity in modern marketing should be considered as a dynamic system of interconnected visual, verbal and value elements that require continuous coordination between digital touchpoints and automated communication processes. Key risks associated with scaling are described, including loss of authenticity, brand fragmentation, and communication imbalances caused by expansion into new markets and the integration of algorithmic decision-making tools. It is noted that the use of artificial intelligence enables large-scale personalization, but this can increase the likelihood of inconsistencies in tone, messages, and the consumer experience in the absence of strategic regulation. The need for implementing integrated brand management systems, modular identity structures, and AI-based personalization mechanisms that align automated processes with predefined brand parameters is justified. Conclusions. Effectively preserving brand identity requires a balance between adaptability and consistency, which is achieved through the synchronization of strategic marketing tools, organizational alignment, and data-driven technologies. By implementing identity principles into both human and algorithmic decision-making processes, small and medium-sized brands can transform artificial intelligence from a source of risk to a strategic asset for sustainable development.